The linkage regarding students’ level of linguistic intelligence and their English academic performance - Alvons Habibie; Wiyanti Wiyanti (English Education Department, 2022)
The goal of this study was to determine the relationship between the students' linguistic intelligence and their success in English learning. The researchers engaged with a quantitative analysis employing a correlational method. This study's population comprised of all 218 students enrolled in SMK Negeri 1 Banggai. 69 eighth-grade students were employed as the sample for this study. In this investigation, the questionnaire and the documentation served as the instruments. Principal data analysis techniques were linear and simple regression analysis. According to the research findings, there was a strong correlation between the linguistic intelligence of eighth-grade students at SMK Negeri 1 Banggai and their success in English academic performance. The correlation formula calculation result (0.611) indicates that there is a significant relationship between these two variables. This indicates that variable x (linguistic intelligence) is positively linked with variable y (English academic performance).